Dual role of select plant based nutraceuticals as antimicrobial agents to mitigate food borne pathogens and as food preservatives1. Issue 94 (14th October 2015) - Subramaniam, Shankar; Rajendran, Narendran; Muralidharan, Sai brinda; Subramaniam, Gayathri; Raju, Ravikumar; Sivasubramanian, Aravind
<x xml:space="preserve">Abstract</x> Dual role of commercially important nutraceuticals from plants that potentiate the therapeutic effect of commercial antibiotics to combat food pathogens.